2017
DOI: 10.2528/pierm16090303
|View full text |Cite
|
Sign up to set email alerts
|

Design of Carbon Nanotube-Based Broadband Radar Absorber for Ka-Band Frequency Range

Abstract: Abstract-The general principles of design and development of microwave absorbing materials are discussed and analysed in respect to 26-37 GHz frequency range (Ka-band). Dispersive composite materials based on carbon nanotubes in epoxy resin matrix are produced, and their electromagnetic responses are investigated in Ka-band. Both theoretical and experimental results demonstrate that presented composites may be used as compact effective absorbers in 26-37 GHz range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…We assume that this special feature of GCS-based monolayer may find some practical applications in the future, for example for designing frequency-selective filters. Also noteworthy is that the microwave absorption performances of the GCSs monolayers considered here are generally comparable with those of other absorbers presented recently [16][17][18] (the absorption mechanism is classical Ohmic losses in conductive medium). These recent reports generally deal with materials based on polymer matrix and their operating temperature range is usually limited below 200-300…”
Section: B Air Gap Dependencesupporting
confidence: 57%
See 1 more Smart Citation
“…We assume that this special feature of GCS-based monolayer may find some practical applications in the future, for example for designing frequency-selective filters. Also noteworthy is that the microwave absorption performances of the GCSs monolayers considered here are generally comparable with those of other absorbers presented recently [16][17][18] (the absorption mechanism is classical Ohmic losses in conductive medium). These recent reports generally deal with materials based on polymer matrix and their operating temperature range is usually limited below 200-300…”
Section: B Air Gap Dependencesupporting
confidence: 57%
“…Generally, the following mechanisms of EM absorption are used for practical a) dzmitrybychanok@ya.ru; www.nano.bsu.by applications: ferromagnetic resonance 10,11 , Ohmic losses 12,13 , dipole relaxation 14 and lossy scattering in metamaterials 15 . At present, many groups focus on the investigation of carbon-based polymer composites for developing effective microwave absorbers [16][17][18] . In this paper, we considered the features of normal scattering of microwave radiation on an ordered monolayer of porous carbon spheres on a Perfect Electrically Conducting (PEC) plate, schematically shown in Fig.1.…”
Section: Introductionmentioning
confidence: 99%
“…The preparation method of hybrid composites (in our case with two different filler types) does not differ essentially from the dispersion of one filler in a polymer matrix [20,24]. The only difference is the separate dispersion of each inclusion (MWCNT and MnFe 2 O 4 ) in ethanol by using ultrasonic devices (bath and probe during 1h each of them).…”
Section: Methodsmentioning
confidence: 99%
“…The integration of separated clusters happen when the concentration of nanotubes approaches a certain critical value. As a result in the system spreading (infinite) cluster is formed, which leads to appearance of the electric contacts between external electrodes in such a compound [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Experimental studies [1] have shown that the conductivity in nanotube polymeric and ceramic matrix materials follows a percolation-like behavior.…”
Section: Introductionmentioning
confidence: 99%